Determinants of phthalate exposure and risk assessment in children from Poland - Mercè Garí; Holger M. Koch; Claudia Pälmke; Agnieszka Jankowska; Ewelina Wesołowska; Wojciech Hanke; Dennis Nowak; Stephan Bose-O'Reilly; Kinga Polańska (Environment International, 2019)
Phthalates are a group of widely used chemicals and humans are exposed to them in their daily life. Some phthalates may affect the hormonal balance in both children and adults. The aim of this study was to assess the phthalate exposure and its determinants among children at age of 7 years from the Polish Mother and Child Cohort Study (REPRO_PL). 250 urine samples collected in 2014–2015 were analysed for 21 metabolites of 11 parent phthalates using on-line high performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS). This represents the most extensive set of phthalate metabolites ever determined for Poland. Ten metabolites were quantifiable in 100% of the samples, another eight in >90%. The highest median concentrations were found for the primary monoester metabolites of di-iso-butyl (MiBP, 72.4 μg/l), di-n-butyl (MnBP, 56.3 μg/l) and diethyl (MEP, 42.0 μg/l) phthalate, followed by the sum of di-2-ethylhexyl (ΣDEHP, 89.3 μg/l) and di-iso-nonyl (ΣDiNP, 21.9 μg/l) phthalate metabolites. Metabolite concentrations were higher in children at 7 years than in the same children at age 2 or in their mothers during pregnancy. Generally, phthalate exposures in this study were much higher than exposures reported in other European populations. Multivariate regression models showed that body mass index, place of residence, breastfeeding duration, socio-economic status and parental education were associated with the metabolite levels in the 7-year old children. Daily intake and hazard index calculations revealed that a small percentage of children (around 3–10%) exceeded the tolerable daily intakes established by international institutions such as EFSA and U.S. EPA indicating that these children might be at risk of anti-androgenic effects from the individual and cumulative exposure to phthalates. Thus, further monitoring of this population, by educational programs and follow-up interventions, is required. Keywords: Birth cohort, Children, Daily intake, Hazard risk, Phthalate metabolites, Poland